Citizens and E-government : evaluating policy and management - Reddick, Christopher G. (Hershey PA : Information Science Reference, 2010)
'This book examines the role that citizens play in the development of electronic government or e-government,specifically focusing on the impact of e-government and citizens, exploring issues of policy and management in government'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Electronic government information; Electronic public records; Government Web sites; Political participation -- Technological innovations